The Effect of Applying A Problem-Based Learning Model Using Google Earth on Understanding Hydrometeorological Disaster Mitigation at SMAN 1 Tanjung Palas Tengah - Bashori, Imam; Khotimah, Nurul (Green Publisher Indonesia, 2024)
This study aims to reveal whether there is a positive influence in the application of the problem-based learning model using google earth media on the understanding of hydrometeorological disaster mitigation in class XI of SMA N1 Tanjung Palas Tengah. The research design used in this study is a nonequivalent control group design with a quasi-experimental research method (Quasi Experiment). The sampling technique used in this research is purposive sample. The research instruments used are test instruments in the form of multiple-choice questions, as well as non-test instruments in the form of observation and documentation. The results of the study showed that there was a positive influence in the application of the problem-based learning model using google earth media on the understanding of hydrometeorological disaster mitigation in class XI at SMAN 1 Tanjung Palas Tengah in the form of a significant increase in the average class score. This is based on the results of N-Gain obtained a value of 66.96% and the t-test obtained a value of Sig. (2-tailed) of 0.001. This is also supported by the results of observational studies that show a positive response from the research subjects.